Phenotypic, Nutritional, and Antioxidant Characterization of Blanched Oenanthe javanica for Preferable Cultivar - Kumar, Sunjeet; Li, Gaojie; Huang, Xinfang; Ji, Qun; Zhou, Kai; Hou, Hongwei; Ke, Weidong; Yang, Jingjing (Frontiers in Plant Science, 2021)
Blanching is a technique used to block the sunlight to get the tender, sweet, and delicious stem in the field. This technique is also used for Oenanthe javanica (also known as water dropwort), an important vegetable in East Asia. However, the effect of blanching on the nutritional level and antioxidant capacity is poorly explored. This study aimed to determine nutrient content and antioxidant capacity for five cultivars and select the best cultivar. The data indicated that blanching significantly influenced the phenotype, physiology, and nutritional level of water dropwort in all cultivars. Although few parameters, such as chlorophyll content, total proteins, polyphenols, and flavonoids decreased with blanching, starch, sugars, vitamins, minerals, and antioxidants activities were increased significantly in the blanched stem in both mid and post blanching periods. The most noticeable changes were detected in post-blanching samples. Furthermore, the cultivar line (V11E0012) was found better than the other four cultivars based on nutritional profile and antioxidant capacity. Therefore, we recommend the use of blanched water dropwort over the un-blanched, and the use of V11E0012 cultivar for blanching cultivation.